Automated breast ultrasound for the detection and reconstruction of the breast ductal pattern. (September 2016) - Kallergi, Maria; Haynes, Mark S.; Bizini, Vicky; Sheth, Paulin A.; Eshraghi, Leah D.; Love, Susan M.
Abstract : Purpose: Automated 3D breast ultrasound (ABUS) has shown several advantages over the conventional handheld systems and promising results in screening women with dense breasts. In addition, ABUS seems to offer a unique opportunity for mapping in vivo the normal ducts thus improving our understanding of normal/malignant relationships in the adult female breast. Preliminary results of such a study are reported here. Materials and methods: Six lactating, nursing volunteers were scanned with the Invenia™ ABUS system (GE Healthcare, WI, USA). The women were imaged before and after breastfeeding their infants. Ductal patterns were generated from the manual segmentations of two experts. Results were qualitatively compared to published work. Descriptive statistics and the t -test were applied to characterize the population and variabilities. Results: Milk filled ducts in lactating women offered a natural contrast agent but empty ducts may also be observed under light breast compression. Most of the ducts were detected and 3D maps were generated. An increased localized activity of milk filled ducts was observed in the lower outer quadrants of all breasts. Ducts from the upper quadrants show involvement in women breastfeeding the longest (11–18 months). Intra- and inter-volunteer variabilities were significant. Conclusion: The ABUS system provided sufficient information to detect and segment most of the breast ducts. The observed localized activity of the ducts agrees with results from prior similar studies and raises new important issues regarding the role of duct involution on cancer development. Further testing is justified as is the development of computer algorithms for automated 3D ductal structure generation.